The Potential Therapeutic Advantages of Bacteriophage Targeting MDR Pseudomonas aeruginosa using the Infection Model of Galleria mellonella - Pooncholai, Kandhan; Dhanaraj, Suresh (Anti-Infective Agents, 2026)
AimThe growing problem of antibiotic-resistant bacteria in clinical environments has driven increased interest in bacteriophage therapy, where viruses specifically target and destroy harmful bacteria. This research explores the therapeutic potential of bacteriophages isolated to combat multi-drug-resistant Pseudomonas aeruginosa, using Galleria mellonella larvae as an experimental model. In vitro susceptibility to multiple antibiotics was assessed using the double agar overlay technique. Additionally, the survival rate of the larvae was analyzed to determine the phages' capacity to combat bacterial infection in G. mellonella. Bacteriophage therapy was employed to treat moth wax larvae that were infected with Multidrug-resistant Pseudomonas aeruginosa.IntroductionResistance to commonly used antibiotics has been steadily increasing over the past few decades, and it has been observed to vary depending on the alternative method employed, such as bacteriophage therapy.Materials and MethodsThe study focused on the Pseudomonas aeruginosa strain PP31, a Multidrug-Resistant Gram Negative bacterium that was obtained from biomedical waste at ICF Hospital in Tamil Nadu, India. Galleria mellonella larvae infected with this multidrug-resistant strain of Pseudomonas were employed for treatment using bacteriophage.ResultsIt was found that a single phage might infect a particular strain of bacteria in the host. It was demonstrated that MDR Pseudomonas aeruginosa infected larvae must be treated with a single specific phage dose (20 µL, 104 PFU/mL) at 6 – hour intervals in order to achieve a 95% survival rate for in vivo research. By counting the number of germs in the larvae, the results were confirmed.ConclusionOur research shows that although phages were shown to be highly contagious in vitro, specific phage dosages were required for effective treatment in living animals.
Keywords: moth wax larvae